2011
DOI: 10.1371/journal.ppat.1002174
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human TLR1 and TLR6 Deficiency with Altered Immune Responses to BCG Vaccination in South African Infants

Abstract: The development of effective immunoprophylaxis against tuberculosis (TB) remains a global priority, but is hampered by a partially protective Bacillus Calmette-Guérin (BCG) vaccine and an incomplete understanding of the mechanisms of immunity to Mycobacterium tuberculosis. Although host genetic factors may be a primary reason for BCG's variable and inadequate efficacy, this possibility has not been intensively examined. We hypothesized that Toll-like receptor (TLR) variation is associated with altered in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 58 publications
3
73
0
2
Order By: Relevance
“…Similarly, Verma et al (2012) found that the C allele of the IL-12Rβ2 promoter significantly impacted TB among Indian patients. Randhawa et al (2011) conducted a different study in South Africa and found that TLR1/6 polymorphisms modulate Th1 T-cell polarization through genetic regulation of monocyte IL-10 secretion in the absence of IL-1 among TB patients. This is the first time that the IL-7Rα +1237 genotypes have been associated with general symptoms such as chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Verma et al (2012) found that the C allele of the IL-12Rβ2 promoter significantly impacted TB among Indian patients. Randhawa et al (2011) conducted a different study in South Africa and found that TLR1/6 polymorphisms modulate Th1 T-cell polarization through genetic regulation of monocyte IL-10 secretion in the absence of IL-1 among TB patients. This is the first time that the IL-7Rα +1237 genotypes have been associated with general symptoms such as chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that the explanation regarding differences in strains may be discounted, as parallel studies in the UK and Malawi using the same strain of vaccine still showed differences in efficacy (8), Keyser et al (25) revealed that BCG substrains had the capacity to drive Th2 immunity and induced variable protection against M. tuberculosis infection (25). Moreover, further study is required with regard to host genetics, as human Toll-like receptor 1 (TLR1) and TLR6-deficiency altered immune responses to BCG vaccination in South African infants (26). In adults and adolescents, pre-exposure to environmental mycobacteria is likely to influence immune responses (27).…”
Section: Discussionmentioning
confidence: 99%
“…While the G allele (serine) is rare, or entirely absent in Africans and Asians, it is the major allele in populations of European descendant (Wong et al 2010). The polymorphism has also been associated with susceptibility to clinical outcomes of malaria (Leoratti et al 2008) and an altered immune response to BCG vaccination, with the same risk allele (Randhawa et al 2011). …”
Section: Host Genetic Background In Lr -mentioning
confidence: 99%